Regulatory Role of Mesenchymal Stem Cells on Secondary Inflammation in Spinal Cord Injury - Pang QM; Chen SY; Fu SP; Zhou H; Zhang Q; Ao J; Luo XP; Zhang T (Dove Medical Press, 2022)
Qi-Ming Pang,1,2 Si-Yu Chen,1 Sheng-Ping Fu,1,2 Hui Zhou,3 Qian Zhang,4 Jun Ao,2 Xiao-Ping Luo,1 Tao Zhang1,2 1Key Laboratory of Cell Engineering of Guizhou Province and Regenerative Medicine Centre, Affiliated Hospital of Zunyi Medical University, Zunyi, People's Republic of China; 2Department of Orthopedics, Affiliated Hospital of Zunyi Medical University, Zunyi, People's Republic of China; 3The First School of Clinical Medicine, Zunyi Medical University, Zunyi, People's Republic of China; 4Department of Human Anatomy, Zunyi Medical University, Zunyi, People's Republic of ChinaCorrespondence: Tao Zhang; Qian Zhang, Email oceanzt@163.com; zmczq@163.comAbstract: Spinal cord injury (SCI) is a catastrophic condition with high morbidity and mortality that still lacks effective therapeutic strategies. It is well known that the most important stage in SCI pathogenesis is secondary injury, and among the involved mechanisms, the inflammatory cascade is the main contributor and directly influences neurological function recovery. In recent years, increasing evidence has shown that mesenchymal stem cells (MSCs) transplantation is a promising immunomodulatory strategy. Transplanted MSCs can regulate macrophage-, astrocyte-, and T lymphocyte-mediated neuroinflammation and help create a microenvironment that facilitates tissue repair and regeneration. This review focuses on the effects of different types of immune cells and MSCs, specifically the immunoregulatory capacity of MSCs in SCI and repair. We will also discuss how to exploit MSCs transplantation to regulate immune cells and develop novel therapeutic strategies for SCI.Keywords: spinal cord injury, mesenchymal stem cells, immune cells, neuroinflammation, immunoregulation, macrophage, astrocyte, T cell